Performance analysis of a stand-alone hybrid energy system for desalination unit in Egypt. (1st July 2020) - Ibrahim, Mostafa M.; Mostafa, Nabil H.; Osman, Ahmed H.; Hesham, Ahmed
Highlights: Analysis of two options of renewable sources for reverse osmosis desalination unit. Optimizing the hybrid system using HOMER software for the proposed two options. Economical study for the optimal case from the two option with COE and LCOW. The levelised cost of water was calculated as 0.56 $/m 3 for hybrid system. Calculate emissions from each case studied and the impact on the environment. Abstract: Renewable energy sources are economical systems suitable for seawater treatment systems wherever there is no electrical grid. This research focuses on finding the best performance of several combinations of these resources (off-grid). The performance compares two alternatives; the first consists of a photovoltaic solar panel, wind turbine, diesel generator, and battery. The second alternative consists of a photovoltaic solar panel, hydrokinetic turbine, diesel generator, and battery. All alternatives are used to drive a small desalination unit with a capacity of 1 m 3 /h. HOMER software is used to optimize the hybrid renewable energy system and perform techno-economic analyses. The optimum case from the first alternative combinations consists of a wind turbine with a rated power of 10 kW, diesel generator with a rated power of 4.90 kW, and 20 kW photovoltaic solar panel. This case achieves the minimum electrical power cost of 0.2252 $/kWh and the corresponding minimum water cost of 1.10$/m 3 . The optimum case from the second alternative combinations consists of a hydrokinetic turbine with a maximum power of 5 kW, diesel generator with a rated power of 4.90 kW, and 2.82 kW photovoltaic solar panel. This case achieves the minimum electrical power cost of 0.1216 $/kWh and the corresponding minimum water cost of 0.56 $/m 3 .